Coupled optical-electrical-thermal simulation for nanoparticles enhanced armorphous silicon solar cells. (September 2021) - Lai, Jia-Jiun; Wong, Basil T.; Chai, Jasman Y-H.
Highlights: Modelling of amorphous silicon solar cell embedded with silver nanoparticles was carried out. Coupled optical-electrical-thermal simulation was developed. Thermal influence on cell optical and electrical performance was investigated. Embedded silver nanoparticles enhance optical and electrical performance of the cell. Abstract: This paper strives to provide a better insight regarding the thermal impact on an amorphous silicon solar cell embedded with silver nanoparticles. Investigation on thermal influence is carried out through simulation modelling. The main aspects considered in modelling are optical, electrical and thermal aspects. The more holistic modelling treatment in this paper introduces various feedback links among three main aspects. Besides thermal impact, this paper provides a preliminary analysis on the factor hindering the nanoparticles embedded from providing satisfactory enhancement on conversion efficiency. The simulation shows that a rise in cell temperature within a range of 32.44K lowers the electrical performance of the cell but promotes a better optical absorption. However, the variations introduced by the rise in temperature are less significant within the simulated temperature range. The key factor that hinders the potential of the nanoparticles lies in the enhanced light spectrum (longer wavelength region).